An Exploratory Study of Gender Role Stress and Psychological Distress of Women in Kosovo - Kaltrina Kelmendi; Liridona Jemini-Gashi (Women's Health, 2022)
Introduction: Although investigations of changing gender roles have been performed globally, most studies have been conducted in high-income countries, and studies from emerging and developing countries are lacking. This study aims to examine the factor structure of the feminine gender role stress scale among women (FGRS) and explore its relationship with psychological distress (PD). Methods: A cross-sectional study was carried out with 656 women from Kosovo using a convenience sampling technique during October 2017 and March 2018. The data were collected through face-to-face interviews and analyzed using the Statistical Package for the Social Sciences version 21 and Mplus 7.3. Confirmatory factor analysis (CFA) and path analysis were used to understand the goodness-of-fit of the FGRS scale in the Kosovo context and explore the relationship between the FGRS scale and PD when treated as latent variables. Multivariance analysis of variance (ANOVA) was used to understand the differences between groups of women based on employment and FGRS. Multinomial logistic regression was used to assess the prediction of different domains of FGRS for PD separately for each category while controlling for age. Results: After demonstrating that the five-factor model of the FGRS showed a good fit to the data in this sample of Kosovo women, analyses revealed that the FGRS domains (fear of victimization and behaving with assertiveness) were positively associated with psychological distress. Conclusion: The findings validate the usefulness of the FGRS scale in a sample of Kosovar women. The intersectionality perspective was used to interpret the importance of multiple layers of vulnerabilities and their coexistence, including education, socioeconomic status, and their implications for health inequalities.